2017
DOI: 10.1021/acs.jafc.6b05721
|View full text |Cite
|
Sign up to set email alerts
|

Arsenic Release from Foodstuffs upon Food Preparation

Abstract: In this study the concentration of total arsenic (As) and arsenic species (inorganic As, arsenobetaine, dimethylarsinate, and methylarsonate) was monitored in different foodstuffs (rice, vegetables, algae, fish, crustacean, molluscs) before and after preparation using common kitchen practices. By measuring the water content of the foodstuff and by reporting arsenic concentrations on a dry weight base, we were able to distinguish between As release effects due to food preparation and As decrease due to changes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
18
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(27 citation statements)
references
References 56 publications
(112 reference statements)
2
18
2
Order By: Relevance
“…For instance, a study performed in Japan that tested the effect of soaking and cooking hijiki on levels of As species found that levels of total arsenic were reduced by ~90% after soaking and subsequent boiling for 20 min (Ichikawa et al 2006). Another study tested how cooking nori and hijiki by soaking and boiling affected As levels (Cheyns et al 2017). The authors found that cooking nori reduced levels of iAs by only 6-24%-although iAs in nori was already low (<0.15 mg/kg)-but cooking hijiki reduced iAs by 70%.…”
Section: Heavy Metalsmentioning
confidence: 99%
“…For instance, a study performed in Japan that tested the effect of soaking and cooking hijiki on levels of As species found that levels of total arsenic were reduced by ~90% after soaking and subsequent boiling for 20 min (Ichikawa et al 2006). Another study tested how cooking nori and hijiki by soaking and boiling affected As levels (Cheyns et al 2017). The authors found that cooking nori reduced levels of iAs by only 6-24%-although iAs in nori was already low (<0.15 mg/kg)-but cooking hijiki reduced iAs by 70%.…”
Section: Heavy Metalsmentioning
confidence: 99%
“…Exactly how much As is actually consumed is even more uncertain as the methods used to prepare and cook rice strongly influence the amount of As ingested. For example, cooking rice with hot water and draining the rice after cooking markedly reduces the amount of As ingested (Cheyns et al 2017;Althobiti et al 2018). Australian drinking water has negligible As, so the absorption of significant amounts of As from water onto rice during the cooking process does not occur (Torres-Escribano et al 2008) as reported in some Asian countries where Ascontaminated drinking water is a major dietary As source (Ackerman et al 2005).…”
Section: Dietary As Intake Total Asmentioning
confidence: 99%
“…As with many other foods, assessment of the risk associated with consumption is usually based on the contaminant contents in the food as it is marketed (fresh or dried), and it does not take into account two aspects that may change the risk substantially: cooking and bioaccessibility (fraction of the element solubilized during digestion and available for intestinal absorption). The few studies on the effect of cooking indicate a decrease in the contents of Hg, Pb, Cd, and As after applying boiling or frying methods to fresh mushrooms (Cheyns, Waegeneers, Van de Wiele & Ruttens, 2017;Cibulka, Čurdová, Miholová & Stěhulová, 1999;Svoboda, Kalač, Špička & Janoušková, 2002). With regard to bioaccessibility, it is necessary to bear in mind that carbohydrates are the main nutrients in mushrooms (35-70% dry weight) and that they are mostly resistant to human digestive enzymes (Cheung, 2013), which could make the solubilization of contaminants during digestion difficult.…”
mentioning
confidence: 99%